EFFECTIVE TEACHING OF A FOREIGN LANGUAGE BASED ON CLIL TECHNOLOGY (KONFERENSIYA, 2026)
Since CLIL is increasingly being seen as a substitute for ELT (EnglishLanguage Teaching), many educators are unsure of what CLIL is and if they shoulduse it. We'll ask language instructors to think about how to enhance not Emphasizestudents' language proficiency and topic knowledge in CLIL instruction in order tofoster an inspiring learning environment whose outcomes will be crucial for theirfuture academic pursuits as well as their professional lives